2020
DOI: 10.1186/s13018-020-02088-5
|View full text |Cite
|
Sign up to set email alerts
|

Controlled fracture of the medial wall versus structural autograft with bulk femoral head to increase cup coverage by host bone for total hip arthroplasty in osteoarthritis secondary to developmental dysplasia of the hip: a retrospective cohort study

Abstract: Background Many methods have been proposed to increase cup coverage by host bone during primary total hip arthroplasty (THA) in hip osteoarthritis secondary to developmental dysplasia of the hip (DDH). However, there was no study comparing the results of controlled fracture of the medial wall with a structural autograft with a bulk femoral head. Methods Sixty-seven hips classified as Crowe II/III were retrospectively included in this cohort study, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Increasing the contact area between the acetabular cup and the host bone can ensure good initial stability, which is a crucial success factor of hip arthroplasty revision. CC is usually used to evaluate this contact area and in DDH hip replacement ( Yang et al, 2017 ; Liu et al, 2018 ; Mou et al, 2020 ; Takasago et al, 2021 ). Generally, insufficient CC will increase the stress at the bone cup interface, thus increasing the probability of mechanical failure ( Apostu et al, 2018 ; Zuo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the contact area between the acetabular cup and the host bone can ensure good initial stability, which is a crucial success factor of hip arthroplasty revision. CC is usually used to evaluate this contact area and in DDH hip replacement ( Yang et al, 2017 ; Liu et al, 2018 ; Mou et al, 2020 ; Takasago et al, 2021 ). Generally, insufficient CC will increase the stress at the bone cup interface, thus increasing the probability of mechanical failure ( Apostu et al, 2018 ; Zuo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…24 Mou et al compared two surgical methods and found that one was better than another in the coverage rate, indicating that the higher the coverage rate, the better. 25 Most previous studies agreed that a higher acetabular coverage rate would give lower revision, 26,27 although this topic is still to be further explored. There is little research reporting the relationship among the Trilogy, the coverage rates and revision rates.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Crowe type II and III DDH with THA may choose to achieve su cient bone coverage for acetabular cup stability by moving the hip joint center upward or inward (7). However, the movement of the rotational center may lead to changes in the biomechanics of the hip joint (8).…”
Section: Introductionmentioning
confidence: 99%